Cyberbullying in Children and Their Legal Consequences According to Positive Law in Indonesia - Nurassani, Sherlie Pramesty (Jurnal Scientia Indonesia, 2020)
This study aims to analyze cyberbullying which includes types, motives, impacts, legal consequences and prevention efforts. This research is a research using a qualitative method, namely a method that focuses on objects through an analytical process and is narrative. There are many bad consequences of the internet, one of which is bullying through the internet or cyberbullying. In general, cyberbullying is a type of crime that is experienced by someone through an electronic device. The crime in question is terror, provocation, evasion, or humiliation carried out through the help of electronic media. Cyberbullying is a threat that results in mental, psychological, and social conditions. Cyberbullying can be prevented as quickly as possible by inviting people to contribute such as parents, teachers, and peers. That is why there is a need for legal protection against perpetrators of the crime of bullying, where the perpetrators also have special rights that should be obtained so that the perpetrators who commit these actions get the legal consequences or sanctions for the actions taken.